Micropipette aspiration of a living cell - Badjo, Wenna (2014)
Micropipette Aspiration (MA) is one of the many techniques to study the mechanical properties of a single cell. In MA, micropipette of diameter smaller than the diameter of the cell is used to apply negative pressure to aspirate on the cell. The aspirated length at its equilibrium will then be measured and used for the analysis of the cell properties. Porcine mesenchymal stem cell (pMSC) will be used for this study. It has been found that cellular environment have an impact on the mechanical properties of the cell. Hence, in this study, it is interested to know the relationship between the two. Polydimethylsiloxane (PDMS) substrate of different stiffness is used for acting as the cellular environment for the pMSC. PDMS is fabricated by mixing the base and curing agent of ratio 5:1, 10:1 and 20:1 repetitively. Cells will be cultured on the PDMS and the properties of cell will be measured on day 1, day 5 and day 7 of the culturing days. Elastic and viscoelastic model were used to analyze the elasticity of the cell. Using the viscoelastic model, it was found that PDMS 20:1 will result in higher stiffness of cell and the longer the cell is cultured on the substrate, the stiffer the cell, however this is only apply for the span of 7 days. On the other hand, no substantiate conclusion is drawn from the elastic modulus. Lastly, the influence of the diameter size of the cell to the stiffness was also studied, however no correlation was found. Hence, for this report, it is concluded that the stiffness of substrate has influenced on the stiffness of cell and pMSC is a viscoelastic cell.